Breast cancer epidemic in the early twenty-first century: evaluation of risk factors, cumulative questionnaires and recommendations for preventive measures - Golubnitschaja, Olga; Debald, Manuel; Yeghiazaryan, Kristina; Kuhn, Walther; Pešta, Martin; Costigliola, Vincenzo; Grech, Godfrey (Tumour biology, 2016)
Rapidly increasing incidence of breast cancer is a new social challenge resulting from a spectrum of internal and external risk factors which appear to be well accepted as an attribute of the early twenty-first century, being, however, new for female sub-populations compared to the past. These include altered socio-economical conditions such as occupational exposure, rotating shift work, specific environmental factors (increased pollution and environmental toxicity, altered dietary habits, quality and composition of meal) as well as consequently shifted and/or adapted physiologic factors such as lower age at menarche, late age of first full-term pregnancy, if any, shorter periods of breastfeeding and later menopause. Consolidated expert statements suggest that over 50 % of all breast cancer cases may be potentially prevented by risk reduction strategy such as regulation of modifiable risk factors. Currently available risk assessment models may estimate potential breast cancer predisposition, in general; however, they are not able to predict the disease manifestation individually. Further, current deficits in risk assessment and effective breast cancer prevention have been recently investigated and summarised as follows: gaps in risk estimation, preventive therapy, lifestyle prevention, understanding of the biology of breast cancer risk and implementation of known preventive measures. This paper overviews the most relevant risk factors, provides recommendations for improved risk assessment and proposes an extended questionnaire for effective preventive measures.
Keywords: Individualised patient profile; Surveys and Questionnaires; Questionnaire; Predictive preventive personalised medicine; Pregnancy; Humans; Guidelines as Topic; směrnice jako téma; Female; rizikové faktory; lidé; průzkumy a dotazníky; Breast Neoplasms; ženské pohlaví; Epidemic; těhotenství; nádory prsu; Breast cancer; Risk Factors